The impact of senescence on muscle wasting in chronic kidney disease. Issue 1 (9th November 2022) - Huang, Ying; Wang, Bin; Hassounah, Faten; Price, S. Russ; Klein, Janet; Mohamed, Tamer M.A.; Wang, Yanhua; Park, Jeanie; Cai, Hui; Zhang, Xuemei; Wang, Xiaonan H.
Abstract: Background: Muscle wasting is a common complication of chronic kidney disease (CKD) that is associated with higher mortality. Although the mechanisms of myofibre loss in CKD has been widely studied, the contribution of muscle precursor cell (MPC) senescence remains poorly understood. Senescent MPCs no longer proliferate and can produce proinflammatory factors or cytokines. In this study, we tested the hypothesis that the senescence associated secretory phenotype (SASP) of MPCs contributes to CKD‐induced muscle atrophy and weakness. Methods: CKD was induced in mice by 5/6th nephrectomy. Kidney function, muscle size, and function were measured, and markers of atrophy, inflammation, and senescence were evaluated using immunohistochemistry, immunoblots, or qPCR. To study the impact of senescence, a senolytics cocktail of dasatinib + quercetin (D&Q) was given orally to mice for 8 weeks. To investigate CKD‐induced senescence at the cellular level, primary MPCs were incubated with serum from CKD or control subjects. The roles of specific proteins in MPC senescence were studied using adenoviral transduction, siRNA, and plasmid transfection. Results: In the hindlimb muscles of CKD mice, (i) the senescence biomarker SA‐β‐gal was sharply increased (~30‐fold); (ii) the DNA damage response marker γ‐H2AX was increased 1.9‐fold; and (iii) the senescence pathway markers p21 and p16 INK4a were increased 1.99‐fold and 2.82‐fold, respectively (all values, P  < 0.05), whereas p53 was unchanged. γ‐H2AX, p21, and p16 INK4A were negatively correlated at P < 0.05 with gastrocnemius weight, suggesting a causal relationship with muscle atrophy. Administration of the senolytics cocktail to CKD mice for 8 weeks eliminated the disease‐related elevation of p21, p16 INK4a, and γ‐H2AX, abolished positive SA‐β‐gal, and depressed the high levels of the SASP cytokines, TNF‐α, IL‐6, IL‐1β, and IFN (all values, P  < 0.05). Skeletal muscle weight, myofibre cross‐sectional area, and grip function were improved in CKD mice receiving D&Q. Markers of protein degradation, inflammation, and MPCs dysfunction were also attenuated by D&Q treatment compared with the vehicle treatment in 5/6th nephrectomy mice (all values, P  < 0.05). Uraemic serum induced senescence in cultured MPCs. Overexpression of FoxO1a in MPCs increased the number of p21 + senescent cells, and p21 siRNA prevented uraemic serum‐induced senescence ( P  < 0.05). Conclusions: Senescent MPCs are likely to contribute to the development of muscle wasting during CKD by producing inflammatory cytokines. Limiting senescence with senolytics ameliorated muscle wasting and improved muscle strength in vivo and restored cultured MPC functions. These results suggest potential new therapeutic targets to improve muscle health and function in CKD.